SSX addiction in melanoma propagates tumor growth and metastasis - Traynor, Sofie; Ebstrup, Malene Laage; Gammelgaard, Odd Lilleng; Mansoori, Behzad; Terp, Mikkel Green; Rein, Cecilie Rose Hauge; Rattenborg, Sofie; Pedersen, Christina Bøg; Ditzel, Henrik Jørn; Gjerstorff, Morten Frier (Frontiers in Oncology, 2022)
Cancer/testis antigens are receiving attention as targets for cancer therapy due to their germ- and cancer cell-restricted expression. However, many of these antigens are inconsistently expressed among cancer types and individual tumors. Here, we show that members of the SSX cancer/testis antigen family comprise attractive targets in the majority of melanoma patients, as SSX is expressed in more than 90% of primary melanomas and metastases and plays a critical role in metastatic progression. Accordingly, SSX silencing in melanoma mouse xenograft models reduced tumor growth and completely abolished the formation of metastatic lesions in lungs and livers. Mechanistically, we demonstrate that silencing SSX in melanoma cells induces cell cycle S-phase stalling, leading to proliferative arrest and enhanced apoptosis, which elucidates the inhibitory effect of SSX loss on tumor growth and colonization capacity. Silencing SSX further compromised the capacity of melanoma cells to migrate and invade, influencing these cells’ capability to spread and colonize. Taken together, these studies highlight SSX proteins as pivotal targets in melanoma with implications for blocking metastatic progression.